Insufficient adherence to the physical exercise of university students. A systematic review - Moreno-Arrebola, R.; Puertas-Molero, P.; Castañeda-Vázquez, C.; Castro-Sánchez, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
A sedentary lifestyle is one of the main problems for the health of the world population of the 21st century. Due to the sociocultural characteristics presented by university students, it is a suitable population for the study and promotion of physical activity (PA). The main aim of the present systematic review is to give a general view on the adherence to the practice of PA among the university population, as well as intervention programs aimed at promoting this practice, from 2007 to the present day. The methodology used has been guided by the PRISMA statement. As main conclusion, 100% of the studies of the first selection support the urgent need for the creation and implementation of intervention programs aimed at promoting the practice of PA among university students. Finally, the intervention programs studied obtained good results, achieving in most of them an increase in the adherence to the practice of PA of the population studied.